A case of duodenal duplication cyst mimicking a pancreatic pseudocyst with intracystic hemorrhage - Sotaro Fukuhara; Saburo Fukuda; Hiroyuki Sawada; Masayuki Shishida; Sho Ishikawa; Kohata Akihiro; Azusa Kai; Yuzoh Hirata; Seiji Fujisaki; Mamoru Takahashi; Hideto Sakimoto (Surgical Case Reports)
Abstract Background Duodenal duplication cysts in adults are rare, and a preoperative diagnosis remains difficult because clinical manifestations are nonspecific and variable. We describe a case of a duodenal duplication cyst mimicking a pancreatic pseudocyst with repeated intracystic hemorrhage. Case presentation A 47-year-old male who complained of upper abdominal pain and vomiting was referred to our hospital. He was a heavy drinker and had a past history of hospitalization for alcoholic chronic pancreatitis. Plain abdominal computed tomography (CT) showed a cystic lesion of 7 cm in size in the lumen near the second part of the duodenum. The cystic lesion showed high density inside. Gastrointestinal endoscopy revealed that the lumen of the duodenum was deformed by a submucosal tumor-like mass and the endoscope could not pass through it, but active bleeding was not seen in the lumen of the duodenum. On the fourth day of hospitalization, anemia progressed and contrast-enhanced CT demonstrated a high-density spot on the wall of the cystic lesion. A pancreatic pseudocyst complicated with intracystic hemorrhage was preliminarily considered. Angiography was immediately performed, and a pseudoaneurysm was identified in the branch of the anterior superior pancreaticoduodenal artery (ASPDA). Transcatheter arterial embolization (TAE) was performed. Anemia did not progress after that, and follow-up CT showed reduction in the size of the cystic lesion. Afterward, the same symptoms recurred twice and surgical treatment was performed for the pancreatic pseudocyst with repeated intracystic hemorrhage. Macroscopically, a cystic mass of 5 cm in size was adjacent to the second part of the duodenum on the pancreas side. A pinhole-sized communication was identified between the cyst and the duodenum lumen. Microscopically, the cyst wall was composed of gastric mucosa and shared a common proper muscle layer with the duodenum. Chronic ulcers and erosions were seen in the cyst. Based on these findings, a diagnosis of duodenal duplication cyst was made. Conclusions Duodenal duplication cysts in adults have seldom been reported and should be considered as a differential diagnosis for a patient with a cystic lesion adjoining the duodenum.